Homotypic targeting and drug delivery in glioblastoma cells through cell membrane-coated boron nitride nanotubes. (July 2020) - De Pasquale, Daniele; Marino, Attilio; Tapeinos, Christos; Pucci, Carlotta; Rocchiccioli, Silvia; Michelucci, Elena; Finamore, Francesco; McDonnell, Liam; Scarpellini, Alice; Lauciello, Simone; Prato, Mirko; Larrañaga, Aitor; et al.
Abstract: Glioblastoma multiforme (GBM) is one of the most aggressive types of brain cancer, characterized by rapid progression, resistance to treatments, and low survival rates; the development of a targeted treatment for this disease is still today an unattained objective. Among the different strategies developed in the latest few years for the targeted delivery of nanotherapeutics, homotypic membrane-membrane recognition is one of the most promising and efficient. In this work, we present an innovative drug-loaded nanocarrier with improved targeting properties based on the homotypic recognition of GBM cells. The developed nanoplatform consists of boron nitride nanotubes (BNNTs) loaded with doxorubicin (Dox) and coated with cell membranes (CM) extracted from GBM cells (Dox-CM-BNNTs). We demonstrated as Dox-CM-BNNTs are able to specifically target and kill GBM cells in vitro, leaving unaffected healthy brain cells, upon successful crossing an in vitro blood-brain barrier model. The excellent targeting performances of the nanoplatform can be ascribed to the protein component of the membrane coating, and proteomic analysis of differently expressed membrane proteins present on the CM of GBM cells and of healthy astrocytes allowed the identification of potential candidates involved in the process of homotypic cancer cell recognition. Graphical abstract: Unlabelled Image Highlights: First example of a biomimetic camouflage of boron nitride nanotubes Evidence of homotypic targeting of boron nitride nanotubes Extensive proteomics investigations describing the homotypic targeting Systematic investigations on in vitro complex systems, including multi-cellular fluidic models and blood-brain barrier models